Counter-case presented on the part of the government of Her Britannic Majesty to the Tribunal of Arbitration constituted under article 1 of the treaty concluded at Washington on the 29th February, 1892 between Her Britannic Majesty and the United States of America [electronic resource]. - Bering Sea Tribunal of Arbitration.; Great Britain. ([London? : s.n., 1893)
Tables. Electronic reproduction. Mode of access: Internet. 44